Rapid Simultaneous Quantitative Analysis of Hypoglycemic agents by RP HPLC: Development, Validation and Application to Medicine - Attimarad, Mahesh; Venugopala, Katharigatta Narayanaswamy; Islam, Mohammed Munirul; Shafi, Sheeba; Altaysan, Abdulrahman Ibrahim (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: For the treatment of diabetes mellitus type 2, a new formulation containing vildagliptin and remogliflozin was developed. A simple and rapid RP-HPLC method employing linagliptin as an internal standard was developed for quality control of this medicine. Methodology: Formulation analytes, including IS, were separated on a Zorbax C18 column with isocratic elution of acetonitrile and phosphate buffer (pH 5) 55:45 v/v at a flow rate of 1.2 mL/min. The experiment was carried out at room temperature and monitored at a wavelength of 210 nm. The approach was also validated in accordance with the ICH Q2 requirements. Results: The optimized HPLC approach revealed a satisfactory linearity in the concentration ranges of 10-60 μg/mL and 10-100 μg/mL for VIL and REM respectively, with good regression coefficient (R2≥0.998). The average accuracy for VL and REM was 99.57 percent and 100.59 percent, respectively, with a low percentage relative error. The method’s precision was proven by the low percentage relative standard deviation. Furthermore, a robustness assessment employing a Pareto chart generated using a three-level factor interaction study, a multivariate technique, demonstrated that minor changes in individual experimental conditions had no effect on the test results. Finally, the optimized HPLC method was effectively used to assess VIL and Rem from formulation simultaneously. Conclusion: The findings of an assay comparing a simple and rapid isocratic RP-HPLC method devised for the simultaneous quantification of VIL and REM to a previously published approach revealed no significant differences in the assay results. As a result, it might be utilized in any analytical laboratory for quality control of this formulation.
Keywords: Vildagliptin; remogliflozin; HPLC method; Validation; Formulation; Robustness; Multivariate